Efektivitas Intervensi Kelompok untuk Meningkatkan Self-Esteem pada Mahasiswa dengan Test Anxiety - Melisa Melisa; Lifina Dewi Pohan (Fakultas Psikologi Universitas Tarumanagara, 2018)
Test is defined as an indicator of success for college students in education. As a result, college students often feel anxious when faced with test and this is called test anxiety. Test anxiety will negatively affect performance’s college students and inhibit student to complete their academic demands. Self-esteem becomes the main factor of college students experiencing test anxiety. The purpose of this study is explain the effectiveness of group intervention in improving self-esteem of college students who experience test anxiety. Intervention is conducted over 4 sessions (90 - 135 minutes each session) by including some strategies such as cognitive restructuring, study skills & habits, self-care, timing, mindfulness, breathing and relaxation techniques, self-control desensitization , and exercises manage distractions. This research method used one group before after design. The number of participants who followed the study were 5 college students. Based on the comparison of pre-test and post-test, the results were as following: (a) the anxiety test score of five participants decreased after therapy; (b) the self-esteem score of three participants increased after therapy. The five participants also showed more adaptable beliefs, decreased physiological reactions, and improved behavior that may degrade performance when dealing with test situations. In addition, all participants began to learn to see the positive qualities within themselves to improve their self-esteem. The results show that group intervention is effective in reducing test anxiety and increasing self-esteemKeywords: Group intervention, self-esteem, test anxiety